Evaluasi Program Usaha Peningkatan Pendapatan Keluarga Sejahtera (UPPKS) Desa Tambaksari, Tirtajaya, Karawang - Sawitri, Eta; Hidayat, Rahmat; Azijah, Dewi Noor (JPAP: Jurnal Penelitian Administrasi Publik, 2021)
This research was based on the UPPKS (Prosperous Family Income Improvement Business) program spearheaded by BKKBN in order to improve welfare and establish a kb program consisting of family stages, especially pre-KS families. The problem started from the number of members of the UPPKS group who joined only slightly compared to the number of people, especially pre-KS in Tambaksari Village, which then raised the question of how the evaluation conducted by the policy implementers. The purpose of this research is to review and analyze the evaluation in the implementation of uppks program tambaksari village district Tirtajaya Karawang regency. The research used qualitative method with case study approach, namely determination of research participants with purposive sampling technique, data collection using observation, interview, documentation, and audio-visual material, as well as data analysis with data reduction, data presentation and conclusion drawing. The results of the research seen from inputs, processes, outputs and overall outcomes have not been able to be carried out optimally both in terms of implementing policies related to human resources and budgets, the way of implementation of activities from socialization, coordination and implementation of participation and support is lacking, and the impact felt in the UPPKS program is not significant.